Factor Analysis Influencing Postoperative Hospital Stay and Medical Costs for Patients with Definite, Suspected, or Unmatched Diagnosis of Acute Cholecystitis according to the Tokyo Guidelines 2013. (28th April 2016) - Hayasaki, Aoi; Takahashi, Koji; Fujii, Takehiro; Kumamoto, Koji; Fujii, Koji; Matsumoto, Eiichi; Miyahara, Shigeki; Kusuta, Tsukasa; Azumi, Yoshinori; Isaji, Shuji
Abstract : Purpose . To identify significant independent preoperative factors influencing postoperative hospital stay (PHS) and medical costs (MC) in 171 patients who underwent cholecystectomy for benign gallbladder diseases and had definite, suspected, or unmatched acute cholecystitis (AC) diagnosis according to the Tokyo Guidelines 2013 (TG13). Methods. The 171 patients were classified according to the combination of diagnostic criteria including local signs of inflammation (A), systemic signs of inflammation (B), and imaging findings (C): A+ B+ C (definite diagnosis, n = 84 ), A+ B (suspected diagnosis, n = 25 ), (A or B) + C (n = 10 ), A (n = 41 ), and B (n = 11 ). Results . The A+ B + C and (A or B) + C groups had equivalent PHS and MC, suggesting that imaging findings were essential for AC diagnosis. PHS and MC were significantly increased in the order of severity grades based on TG13. Performance status (PS), white blood cell count, and severity grade were identified as preoperative factors influencing PHS by multivariate analysis, and significant independent preoperative factors influencing MC were age, PS, preoperative biliary drainage, hospital stay before surgery, albumin, and severity grade. Conclusion . PS and severity grade significantly influenced prolonged PHS and increased MC.